Group living in highland tuco-tucos (Ctenomys opimus) persists despite a catastrophic decline in population density - Lacey, Eileen (2024)
Identifying the factors that favor group living is central to studies of animal social behavior.One demographic parameter that is expected to substantially shape spatial and social relationshipsis population density. Specifically, high population densities may favor group livingby constraining opportunities to live alone. In contrast, low densities may allow individuals tospread out within the habitat, leading to a reduction in the prevalence or size of socialgroups. Abrupt changes in density following natural catastrophic events provide importantopportunities to evaluate the effects of population density on patterns of spatial and socialorganization. As part of long-term studies of the behavioral ecology of a population of highlandtuco-tucos (Ctenomys opimus) at Monumento Natural Laguna de los Pozuelos, JujuyProvince, Argentina, we monitored the demographic and behavioral consequences of aflood that inundated our study site during December 2012. Unlike most species of Ctenomysstudied to date, highland tuco-tucos are group living, meaning that multiple adults share burrowsystems and nest sites. Despite a post-flood reduction in population density of ~75%,animals present on the study site during the 2013 breeding season continued to live in multiadultsocial units (groups). No differences between pre- and post-flood home range sizeswere detected and although between-unit spatial overlap was reduced in 2013, overlapwithin social units did not differ from that in pre-flood years. Animals assigned to the samesocial unit in 2013 had not lived together during 2012, indicating that post-flood groups werenot simply the remnants of those present prior to the flood. Collectively, these findings indicatethat group living in highland tuco-tucos is not driven by the density of conspecifics in thehabitat. In addition to enhancing understanding of the adaptive bases for group living in Ctenomys,our analyses underscore the power of catastrophic events to generate insights intofundamental aspects of social behavior.